EXTREMELY SEVERE COURSE OF A NEW CORONAVIRUS INFECTION IN A PREGNANT WOMAN - Светлана Ивановна Елгина; Ольга Сергеевна Золоторевская; Екатерина Владимировна Грищенко; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес (Медицина в Кузбассе, 2022)
Vulvar cancer (RV) is a malignant neoplasm arising from the integumentary flat epithelium of a woman's external genitalia. In the etiology and pathogenesis of RV, 2 factors play a leading role: age-related involutive-atrophic processes of the external genitalia and infection with human papillomavirus (HPV). In 90 % of cases, squamous cell carcinoma is morphologically verified – a malignant neoplasm arising from the integumentary flat epithelium of the external genitalia of a woman. RV accounts for 1 % of all cancer cases in women. In the structure of the incidence of malignant neoplasms of the female genital organs, the share of primary RV is about 2-5 %. In 2018, the incidence of RV in Russia was 2.6 cases per 100 thousand women, which in absolute numbers amounted to 2060 cases. A clinical case of vulvar cancer is presented.